Institutional moral hazard in the multi-tiered regulation of unemployment and social assistance benefits - Vandenbroucke, Frank; Luigies, Chris (Brussels, 2016)
"This paper studies eight countries in which the regulation of unemployment benefits and related benefits and the concomitant activation of unemployed individuals has a multi-tiered architecture. It assesses their experiences and tries to understand possible problems of ‘institutional moral hazard’ that may emerge in the context of a hypothetical European Unemployment Benefit Scheme.